Pediatricians’ perception of factors concerning the clinical application of blockchain technology to pediatric health care: a questionnaire survey - Yong Sauk Hau; Min Cheol Chang; Jae Chan Park; Young Joo Lee; Seong Su Kim; Jae Min Lee (Journal of Yeungnam Medical Science, 2023)
Background Interest in digital medical information has increased because it allows doctors to easily access a patient’s medical records and provide appropriate medical care. Blockchain technology ensures data safety, reliability, integrity, and transparency by distributing medical data to all users over a peer-to-peer network. This study attempted to assess pediatricians’ thoughts and attitudes toward introducing blockchain technology into the medical field. Methods This study used a questionnaire survey to examine the thoughts and attitudes of 30- to 60-year-old pediatricians regarding the introduction of blockchain technology into the medical field. Responses to each item were recorded on a scale ranging from 1 (never agree) to 7 (completely agree). Results The scores for the intentions and expectations of using blockchain technology were 4.0 to 4.6. Pediatricians from tertiary hospitals responded more positively (4.5–4.9) to the idea of using blockchain technology for hospital work relative to the general population (4.3–4.7). However, pediatricians working in primary and secondary hospitals had a slightly negative view of the application of blockchain technology to hospital work (p=0.018). Conclusion When introducing the medical records of related pediatric and adolescent patients using blockchain technology in the future, it would be better to conduct a pilot project that prioritizes pediatricians in tertiary hospitals. The cost, policy, and market participants’ perceptions are essential factors to consider when introducing technology in the medical field.